תשובה:
# x ^ 2 + 2x-8 = 0 #
# (+ 2) -sqrt (2) 2-4 * 1 * (- 8)) / (2 * 1) = (+ 2) -sqrt (36)) / (2) = (+ 2) -6) / (2) #
#x = (- 2-6) / (2) = (- 8) / (2) = - 4 #
#x = (- 2 + 6) / (2) = (4) / (2) = 2 #
# y = (x + 4) (x-2) #
הסבר:
אם אתה רוצה גורם # x ^ 2 + 2x-8 #.
בחירת משוואה ריבועית כדי גורם.
# x ^ 2 + 2x-8 = 0 #
#x = (- b + -qqrt (b ^ 2-4ac)) / (2a) #
איפה # a = 1, b = 2 # ו # c = -8 #
# (+ 2) -sqrt (2) 2-4 * 1 * (- 8)) / (2 * 1) = (+ 2) -sqrt (36)) / (2) = (+ 2) -6) / (2) #
אשר ייתן, #x = (- 2-6) / (2) = (- 8) / (2) = - 4 #
בנוסף, #x = (- 2 + 6) / (2) = (4) / (2) = 2 #
הטופס המאוחד שלך יהיה, # (x + 4) (x-2) #